2012
DOI: 10.1007/s11250-012-0155-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of HSP genes during different seasons in goats (Capra hircus)

Abstract: The present study has demonstrated the expression of HSP60, HSP70, HSP90, and UBQ in peripheral blood mononuclear cells (PBMCs) during different seasons in three different age groups (Groups I, II, and III with age of 0-2, 2-5, and >5 years, respectively) of goats of tropical and temperate regions. Real-time polymerase chain reaction was applied to investigate mRNA expression of examined factors. Specificity of the desired products was documented using analysis of the melting temperature and high-resolution ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
41
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 30 publications
22
41
0
3
Order By: Relevance
“…In the present study, we observed that HSP70 mRNA expression was found to be significantly higher (P<0.05) during the summer in both breeds in comparison with the winter season. Our findings are in accordance with previous studies in which heat stress-induced HSP70 expression was observed in the goat PBMCs (Banerjee et al 2014;Dangi et al 2012) and bovine lymphocytes (Lacetera et al 2006;Upadhyay 2007, 2010). During the winter, HSP70 expression was approximately three times higher in Ghungroo compared to LWY.…”
Section: Hsp70supporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, we observed that HSP70 mRNA expression was found to be significantly higher (P<0.05) during the summer in both breeds in comparison with the winter season. Our findings are in accordance with previous studies in which heat stress-induced HSP70 expression was observed in the goat PBMCs (Banerjee et al 2014;Dangi et al 2012) and bovine lymphocytes (Lacetera et al 2006;Upadhyay 2007, 2010). During the winter, HSP70 expression was approximately three times higher in Ghungroo compared to LWY.…”
Section: Hsp70supporting
confidence: 93%
“…Its major functions are protein folding, cytoprotection, and as molecular chaperones (Dangi et al 2012). In the present study, we observed that HSP70 mRNA expression was found to be significantly higher (P<0.05) during the summer in both breeds in comparison with the winter season.…”
Section: Hsp70supporting
confidence: 50%
See 2 more Smart Citations
“…plasma cortisol levels, but acute exposure to high temperatures (in the range of 40°C as observed during summer in the present experiments) increases plasma cortisol levels and triggers other stress responses such as the expression of HSP in PBMC (Dangi et al, 2012;Sharma et al, 2013). These non-linear effects of increased temperature on HPA axis activity can explain apparently divergent experimental results of the effects of seasons, depending on the range of temperatures encountered at each experimental location.…”
Section: Adaptation To Heat Reducesmentioning
confidence: 55%